SEMANGAT KERJA DAN GAYA KEPEMIMPINAN - Asnawi, Sahlan (Faculty of Psychology, Universitas Gadjah Mada, 1999)
The research was intended to find the affect of the leadership style on work-enthusiasm. Hypothesis was stated that employees who have relationorientation leader would increase their work-enthusiasm. The subject of the research was 100 employees. Data were obtained by Leadership style Scale and Work-enthusiasm scale. The result shows that there is no significant difference on the work enthusiasm between the relationorientation leader and task-orientation leader. The hypothesis is inconsistent with the study result. Keywords: Leadership-style, work-enthusiasm.